An industrial quality control study on Del Monte Philippines, Incorporated - Boyonas, Mark Ismael V. (College of Engineering, 2002)
Del Monte Philippines, Incorporated is one of the largest producers of processed pineapple in the country. It currently produces an average of 1459 metric tons of canned pineapple per day. Canned sliced pineapple represents at least 60 percent of this production size. The statistical analysis study focuses on canned sliced pineapple which, aside from being the bulk of production of processed fruit solids, is also known to have a manufacturing process that is very much similar to that of other pineapple product styles like chunks and tidbits which are just residual products of sliced pineapple. The production process starts from the harvesting of the fruit in the plantation to its processing and packing. At almost every step, quality inspection is done to assure consumers of the quality they had known Del Monte products to have. In some cases like the slicing of the pineapple, 100 percent visual inspection is being done. The study focused on the potential savings the company can have once process improvements are implemented. Observations on the process mean of fill-weight in canned sliced pineapple indicated that the process is currently overfilling by the amount of 0.1 oz. per can. Converted into an annual lost sales from yield losses, it amounted to a whopping 6 million pesos. The problems identified in the study are as follows, irregular fruit slice cuts, non-uniform ripeness of the fruit, and the overfilling of the syruping machine. For these problems alternatives for solution are proposed. Various tools such as Control charting, Process Capability analysis, Quality Cost analysis, Factorial design and Failure Mode Effects Analysis were used to infer process characteristics. These tools were used to support the claims in the problem analysis. Analysis from the process capability computations, indicate that the current process is inadequate for the present specifications. This implies that currently the company produces products that are mostly out of specifications. From the plotting of the control chart it was found out that the current process mean for the fruit fill-weight is over the specification by 0.1 ounces. This implies that currently the company is incurring yield losses from producing overweight products. It was recommended that actions should be taken to correct this. Proposals such as the regular calibration of the slicer, conveyors, syrrupers, as well as doing additional agricultural research were evaluated against their potential benefits. The implementation of these proposals will entail teamwork from different departments as well as higher management support.